2018
DOI: 10.1371/journal.pone.0208579
|View full text |Cite
|
Sign up to set email alerts
|

A paradoxical method to enhance compensatory lung growth: Utilizing a VEGF inhibitor

Abstract: Exogenous vascular endothelial growth factor (VEGF) accelerates compensatory lung growth (CLG) in mice after unilateral pneumonectomy. In this study, we unexpectedly discovered a method to enhance CLG with a VEGF inhibitor, soluble VEGFR1. Eight-week-old C57BL/6 male mice underwent left pneumonectomy, followed by daily intraperitoneal (ip) injection of either saline (control) or 20 μg/kg of VEGFR1-Fc. On post-operative day (POD) 4, mice underwent pulmonary function tests (PFT) and lungs were harvested for volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Preeclampsia is characterized by an imbalanced maternal angiogenic state, resulting in generalized endothelial dysfunction, increased levels of maternal antiangiogenic factor soluble fms-like tyrosine kinase-1 (sFlt-1), and decreased free circulating levels of the angiogenic factors vascular endothelial growth factor (VEGF) and placental growth factor 2023 . VEGF is important for normal lung vasculature 24 and surfactant protein production 2527 . sFlt-1, an antagonist of VEGF, can impede VEGF signaling and lead to impaired surfactant production.…”
Section: Discussionmentioning
confidence: 99%
“…Preeclampsia is characterized by an imbalanced maternal angiogenic state, resulting in generalized endothelial dysfunction, increased levels of maternal antiangiogenic factor soluble fms-like tyrosine kinase-1 (sFlt-1), and decreased free circulating levels of the angiogenic factors vascular endothelial growth factor (VEGF) and placental growth factor 2023 . VEGF is important for normal lung vasculature 24 and surfactant protein production 2527 . sFlt-1, an antagonist of VEGF, can impede VEGF signaling and lead to impaired surfactant production.…”
Section: Discussionmentioning
confidence: 99%
“…As these patients are susceptible to postoperative complications and respiratory failure, conservative management of the remaining lung may not be adequate to improve quality of life. Present studies have been aiming to develop treatments that can actively improve pulmonary function after a pneumonectomy [113][114][115][116][117][118][119][120][121][122][123][124][125]. Among these studies, post-pneumonectomy compensatory lung growth seems to be especially promising.…”
Section: Respiratory Healthmentioning
confidence: 99%
“…There are two novel methods that potentially stimulate compensatory lung growth after a pneumonectomy: the administration of VEGF receptor 1 (VEGFR1) and erythropoietin (EPO). A recent study reported that the systemic administration of VEGFR1, a VEGF inhibitor, stimulated angiogenesis and increased lung volume of mice [120]. VEGFR1 increased the level of VEGF and VEGFR2 in the lung, enhancing endothelial proliferation and pulmonary surfactant production [120].…”
Section: Respiratory Healthmentioning
confidence: 99%
See 2 more Smart Citations